Method for regenerating waste positive electrode material through oxalic acid surface modification
Through oxalic acid surface modification and high-temperature roasting technology, the failure problem of the cathode material of waste lithium battery is solved, the morphology and performance repair of the material is achieved, the cycle stability is improved, and the cost is reduced, and it has high industrialization potential.
Patent Information
- Application Number
- CN202411309979.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-19
AI Technical Summary
The prior art is difficult to effectively repair and regenerate nickel-rich ternary layered oxide cathode materials in waste lithium batteries. Especially after the nickel content increases, its failure degree is intensified, resulting in the generation of LiF impurities and inactive NiO, which increases. The difficulty of material repair and recovery of regenerated electrode material performance is achieved.
Through the oxalic acid surface modification and high-temperature roasting process, mechanically activated surface modification converts the polycrystalline particles of the waste positive electrode material into a uniform single crystal form, removes LiF impurities on the surface, and forms a stable oxalate structure to improve material circulation, thereby improving material circulation. stability.
It significantly improves the morphology and performance repair effect of waste positive electrode materials, reduces the interface side reaction between the electrode and the electrolyte, improves the cyclic stability of the electrode, and uses common and low-cost industrial raw materials, with simple operation steps and High industrial potential.
Smart Images

Figure CN119297456A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium batteries, and in particular to a method for regenerating waste positive electrode materials through surface modification with oxalic acid. Background Art
[0002] The rapid popularity of electric vehicles around the world has led to a sharp increase in the demand for lithium-ion batteries (LIBs), which has resulted in a large number of retired batteries, exacerbating resource and environmental pressures. The recycling of waste LIBs has become critical, especially for LiNi, which is rich in lithium, cobalt, nickel, and manganese. x Co y Mn 1-x-y O2 (NCM) ternary layered oxide positive electrode materials have shown significant economic and environmental value in the field of battery recycling. In recent years, the direct repair and regeneration technology of ternary positive electrode materials has gradually attracted attention due to its advantages such as short process flow, low energy consumption and high returns. However, with the increase of nickel content in NCM materials, its failure degree will be significantly aggravated, and more LiF impurities and inactive NiO will be produced during the cycle process, which not only increases the difficulty of material repair and regeneration, but also limits the recovery of the performance of the regenerated electrode material.
[0003] Therefore, how to provide a regeneration method to achieve efficient repair of the morphology and performance of waste lithium battery positive electrode materials is an urgent problem that technicians in this field need to solve. Summary of the invention
[0004] In view of this, the present invention provides a method for regenerating waste positive electrode materials through oxalic acid surface modification, and the regeneration method can achieve efficient repair of the morphology and performance of waste positive electrode materials through mechanical activation surface modification and high-temperature calcination process.
[0005] In order to achieve the above object, the present invention adopts the following scheme:
[0006] In one aspect, the present invention provides a method for regenerating waste positive electrode materials by surface modification with oxalic acid, comprising the following steps:
[0007] (1) separating and drying the waste positive electrode material and the oxalic acid solution after ball milling to obtain a modified material;
[0008] (2) The modified material and a lithium source are mixed and calcined to obtain a regenerated positive electrode material.
[0009] Preferably, the ball milling has a rotation speed of 450-500 rpm and a duration of 25-35 min.
[0010] Preferably, the ball-to-material ratio of the ball milling process is (18-28):1.
[0011] Preferably, the oxalic acid solution is prepared by mixing oxalic acid and water in a ratio of (0.1-0.75) g: (30-70) ml.
[0012] Preferably, the molar ratio of the waste positive electrode material and oxalic acid is (1.4-2.8):5.
[0013] Preferably, an oxalate coating layer with a thickness of 1.2-2.8 nm is formed on the surface of the modified material, and the morphology is single crystal particles, and the particle size of the single crystal particles is 0.5-2 μm.
[0014] Preferably, the molar ratio of the lithium element in the lithium source to the transition metal element in the waste positive electrode material is (1-1.1):1.
[0015] Preferably, the lithium source includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate.
[0016] Preferably, the calcination includes a first calcination and a second calcination performed sequentially, wherein the first calcination is performed at a temperature of 450-550° C. for 1.5-2.5 h; and the second calcination is performed at a temperature of 800-900° C. for 13-17 h.
[0017] Preferably, the waste positive electrode material comes from a nickel-cobalt-manganese ternary lithium battery.
[0018] Preferably, washing and centrifugation steps are included between the separation and drying.
[0019] On the other hand, the present invention also provides a regenerated positive electrode material prepared by any of the above methods for regenerating waste positive electrode materials by surface modification with oxalic acid.
[0020] The present invention provides a method for regenerating waste positive electrode materials by surface modification with oxalic acid. Compared with the prior art, the method has the following beneficial effects:
[0021] The present invention introduces oxalic acid during the mechanical activation surface modification process, successfully modifies the transition metal oxide structure on the surface of the waste NCM material into an oxalate structure, and simultaneously depolymerizes the broken polycrystalline particles and transforms them into a uniform single crystal form, completely removing the LiF impurities on the surface, and eliminating the influence of the impurities on the repair process and the regenerated material; the material surface-modified and repaired with oxalic acid exhibits less structural degradation during the cycle process, and simultaneously forms a more stable CEI film, effectively reducing the interface side reactions between the electrode and the electrolyte, thereby significantly improving the cycle stability of the electrode.
[0022] In the regeneration process of the waste positive electrode material of the present invention, common and low-cost industrial raw materials such as water and oxalic acid are mainly used, and the operation steps are simple and easy to implement, and the method has high industrialization potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0024] Figure 1 This is the SEM image of 622-S in Comparative Example 1;
[0025] Figure 2 is the SEM image of 622-HCO-MA in Example 1;
[0026] Figure 3 is the SEM image of the modified material in Example 2;
[0027] Figure 4 is the SEM image of the modified material in Example 3;
[0028] Figure 5 is the SEM image of the modified material in Example 4;
[0029] Figure 6 is the SEM image of the modified material in Example 5;
[0030] Figure 7 is the XRD pattern of the modified material after mechanical activation in Examples 1-5;
[0031] Figure 8 Thermogravimetric curves of the modified materials after mechanical activation in Example 1 and Examples 3-5;
[0032] Fig. 9 TEM image of the 622-HCO-MA material after mechanical activation in Example 1;
[0033] Fig.10 It is the O1s spectrum of XPS of 622-S in Comparative Example 1 and 622-HCO-MA in Example 1;
[0034] Fig.11 It is the F1s spectrum of XPS of 622-S in Comparative Example 1 and 622-HCO-MA in Example 1;
[0035] Fig.12 is the SEM image of the regenerated 622-HCO-R material in Example 5;
[0036] Fig.13 The test results of the cycle performance of the regenerated electrode materials in Examples 1-4;
[0037] Fig.14 The test results of the cycle performance of the regenerated electrode materials in Example 1, Example 5 and Example 6;
[0038] Fig.15 Cyclic performance test results of 622-S in Comparative Example 1, and the regenerated electrode materials in Comparative Example 2 and Example 5;
[0039] Fig.16 This is the F1s spectrum obtained by XPS testing the electrode pieces of the regenerated electrode materials of Comparative Example 2 and Example 5 after the cycle test. DETAILED DESCRIPTION
[0040] The present invention will be described below by specific examples, and it will be appreciated by those skilled in the art that the following specific examples are only for illustrative purposes, and do not limit the scope of the present invention in any way. In addition, in the following examples, unless otherwise specified, the reagents and equipment used are all commercially available. If in the following examples, specific treatment conditions and treatment methods are not clearly described, then conditions and methods known in the art can be used to process.
[0041] In one aspect of the present invention, the present invention provides a method for regenerating waste positive electrode materials by surface modification with oxalic acid, comprising the following steps:
[0042] S100. Dissolve oxalic acid in water to obtain an oxalic acid solution.
[0043] In this step, the oxalic acid solution is prepared by mixing oxalic acid and water in a ratio of (0.1-0.75) g: (30-70) ml, preferably in a ratio of (0.38-0.5) g: (45-55) ml.
[0044] S200. The waste positive electrode material and the oxalic acid solution are ball-milled in a ball mill, and then separated, washed, centrifuged and dried to obtain a modified material.
[0045] In this step, the waste positive electrode material comes from a nickel-cobalt-manganese ternary lithium battery, and the ternary positive electrode material includes LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.5 Co 0.2 Mn 0.3 O2 or LiNi 0.8 Co 0.1 Mn 0.1 O2, preferably LiNi 0.6 Co 0.2 Mn 0.2 O2.
[0046] The molar ratio of the waste positive electrode material to oxalic acid is (1.4-2.8):5, preferably (2-2.5):5. When the amount of oxalic acid added increases, the surface content of the modified oxalate increases.
[0047] The rotation speed of the ball mill is 450-500 rpm, and the duration is 25-35 min; preferably, the rotation speed of the ball mill is 475-485 rpm, and the duration is 25-35 min; the ball-to-material ratio of the ball milling process is (18-28):1, preferably (24-26):1, and the faster the rotation speed of the ball milling process, the faster the particle deagglomeration speed.
[0048] In the separation, washing, centrifugation and drying process, deionized water is used for filtration, washing 5-10 times, centrifugation at 8000-12000rpm, and drying at 70-90°C air atmosphere for 10-15h. More preferably, washing is performed 8 times, centrifugation is performed at 9900-10500rpm, and drying is performed at 78-82°C air atmosphere for 10-12h.
[0049] An oxalate structure is formed on the surface of the modified material, the thickness of the oxalate coating layer is 1.2-2.8 nm, preferably 1.8-2.2 nm, the morphology is single crystal particles, and the particle size of the single crystal particles is 0.5-2 μm, preferably 0.8-1.2 μm.
[0050] The present invention introduces oxalic acid during the mechanical activation process, successfully modifies the surface of waste NCM materials into an oxalate structure, and transforms broken polycrystalline particles into a uniform single crystal form, while completely removing LiF impurities on the surface, eliminating the influence of impurities on the repair process and recycled materials.
[0051] S300. Adding a lithium source to the modified material, and calcining the resulting mixture under an oxygen atmosphere to obtain a regenerated positive electrode material.
[0052] In this step, the molar ratio of the lithium element in the lithium source to the transition metal element in the waste positive electrode material is (1-1.1):1, preferably 1.05:1; the lithium source includes one or more of lithium hydroxide, lithium carbonate, and lithium nitrate, preferably lithium hydroxide.
[0053] The calcination includes a first calcination and a second calcination performed sequentially, wherein the first calcination is performed at a temperature of 450-550°C, preferably 490-510°C, and the time is 1.5-2.5h, preferably 1.9-2.1h; the second calcination is performed at a temperature of 800-900°C, preferably 845-855°C, and the time is 13-17h, preferably 15.5-16.5h.
[0054] In another aspect of the present invention, the present invention further provides a regenerated positive electrode material, which is regenerated using the method described above. Therefore, the regenerated positive electrode material has all the characteristics and preferences possessed by the method described above, which will not be repeated here.
[0055] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0056] Example 1
[0057] Reduce the battery capacity to 75% of the original capacity of the waste ternary lithium battery (the positive electrode material is LiNi 0.6 Co 0.2 Mn 0.2 O2) was fully discharged by a discharge machine and then disassembled in a glove box filled with inert argon. The positive and negative electrodes were manually separated to obtain the positive electrode sheet. After calcination at 600°C for 3h, the binder and conductive carbon were removed to obtain the positive electrode material powder to be repaired, named 622-S.
[0058] 0.4 g of oxalic acid was fully dissolved in 50 mL of water, 1 g of 622-S material was placed in a 100 mL ball mill, oxalic acid solution was added, and mechanical activation was performed at a rotation speed of 480 rpm for 30 min, wherein the molar ratio of oxalic acid to waste positive electrode material was 2.2:5; the powder was separated, washed and centrifuged multiple times, and dried at 80°C for 12 h to obtain an oxalic acid surface-modified material, named 622-HCO-MA.
[0059] The elemental composition of 622-HCO-MA material was tested by ICP-OES, and LiOH·H2O was supplemented according to the stoichiometric ratio of lithium and transition metal elements of 1.05:1. After the materials were mixed evenly, they were calcined at high temperature in an oxygen atmosphere at 500°C for 2h and then at 800°C for 16h. The obtained recycled material was named 622-HCO-R.
[0060] Example 2
[0061] The only difference between this embodiment and embodiment 1 is that the mechanical activation medium is 50 mL of distilled water, and no oxalic acid is added. The remaining operation steps are the same as those in embodiment 1.
[0062] Example 3
[0063] The only difference between this embodiment and embodiment 1 is that the ratio of the amount of oxalic acid to the amount of waste positive electrode material is 0.6:5, and the remaining operating steps are the same as those in embodiment 1.
[0064] Example 4
[0065] The only difference between this embodiment and embodiment 1 is that the ratio of the amount of oxalic acid to the amount of waste positive electrode material is 1.4:5, and the remaining operating steps are the same as those in embodiment 1.
[0066] Example 5
[0067] The only difference between this embodiment and embodiment 1 is that the ratio of the amount of oxalic acid to the amount of waste positive electrode material is 2.8:5, and the remaining operating steps are the same as those in embodiment 1.
[0068] Example 6
[0069] The only difference between this embodiment and embodiment 1 is that the calcination conditions are calcination at 500° C. for 2 h and then calcination at 850° C. for 16 h. The remaining operating steps are the same as those in embodiment 1.
[0070] Example 7
[0071] The only difference between this embodiment and embodiment 1 is that the calcination conditions are calcination at 500° C. for 2 h and then calcination at 900° C. for 16 h. The remaining operating steps are the same as those in embodiment 1.
[0072] Comparative Example 1
[0073] The difference between this comparative example and Example 1 is that the molecular formula of the waste lithium battery positive electrode material 622-S is Li 0.83 Ni 0.6 Co 0.2 Mn 0.2 O2.
[0074] Comparative Example 2
[0075] The only difference between this comparative example and Example 1 is that the waste lithium battery positive electrode material 622-S is not subjected to surface modification treatment by mechanical activation with oxalic acid, but is directly obtained by lithium supplementation and high-temperature calcination repair.
[0076] The present invention conducted SEM tests on the samples of the waste lithium battery positive electrode materials after mechanical activation in Comparative Example 1 and Examples 1-5. Figure 1 It can be seen that the morphology of the waste ternary positive electrode material 622-S in comparative example 1 is a broken secondary sphere with cracking. Figures 2 to 6 It can be seen that: in Example 2, no oxalic acid was added, and its morphology still maintained the characteristics of 622-S particles, showing a large number of broken secondary particles with irregular shapes, indicating that the particle morphology changed little without adding oxalic acid; after oxalic acid was added to the system, it can be observed that the secondary particles were depolymerized, and the particles began to become smaller and more uniform; among them, the secondary particles of the 622-HCO-MA material of Example 1 have been completely depolymerized, and their morphology is shown as more uniform primary particles.
[0077] The present invention uses XRD characterization technology to compare the changes in the crystal structure of the electrode material before and after oxalic acid surface modification, and obtains the XRD spectra of the modified materials of Examples 1-5 after mechanical activation. The results are shown in Figure 7 The results show that the XRD spectra of the modified materials of Example 1 and Example 5 show characteristic peaks of transition metal oxalate at around 22.6° and 30.2°, while there are no obvious characteristic peaks of oxalate in the modified materials of Examples 2-4, and as the amount of oxalic acid added increases, the characteristic peaks of transition metal oxalate in the XRD spectra gradually become stronger, indicating that the amount of oxalic acid added directly affects the formation of the surface structure of oxalate.
[0078] On this basis, the thermogravimetric (TG) curves of NCM622 materials prepared with different oxalic acid additions were analyzed. Figure 8 It can be seen that the samples prepared with different oxalic acid additions showed different mass losses during the heating process. The thermogravimetric curve showed two obvious weight losses starting from 100°C and 200°C. These two stages represent the evaporation of water and the decomposition of oxalate, respectively, and the decomposition reaction lasted until about 500°C. In Examples 1, 4, and 5, a weight loss peak obviously belonging to the decomposition of oxalate was detected, indicating that an oxalate surface was prepared under this condition. By comparing the weight loss percentages of different samples, it can be found that with the increase in the amount of oxalic acid added, the mass loss of the sample during the heating process gradually increased, which also shows that the content of oxalate structure in the sample increases, further clarifying the effect of the amount of oxalic acid added on the surface structure of the prepared NCM622 material.
[0079] The present invention uses TEM detection technology to characterize the surface structure of the material after mechanical activation surface modification in Example 1. The detection results are shown in Fig. 9 In the TEM image, it can be seen that a uniform coating layer with a thickness of about 2 nm is formed on the surface of the 622-S material. This result shows that a uniform and dense oxalate surface structure is successfully prepared on the surface of the waste NCM material by means of auxiliary mechanical activation in an oxalic acid environment.
[0080] The present invention conducted XPS tests on the materials before and after mechanical activation with oxalic acid, and analyzed the changes in the chemical state of the surface elements of the materials before and after oxalate modification. The O 1s test results are shown in Fig.10 , F 1s test results see Fig.11 As can be seen from the figure, the O1s spectrum mainly contains two characteristic peaks. ImpurityThe peak ratio is significantly enhanced, indicating that the number of surface oxalate structures has increased, which provides further evidence for the successful preparation of the oxalate surface structure. In the F1s spectrum of 622-HCO-MA, the strong LiF peak (684.8 eV) originally in the 622-S sample is completely removed, indicating that the oxalate surface modification process completely removes the LiF impurities on the surface of the waste electrode material.
[0081] like Fig.12 The SEM image of the regenerated 622-HCO-R material obtained in Example 5 of the present invention is shown. The present invention tests the charge-discharge cycle performance of the electrode materials regenerated in Comparative Example 1, Comparative Example 2 and Examples 1-7, and cycles 100 times at a rate of 0.5C. The test results are shown in FIG. Fig.13 , Fig.14 and Fig.15 .from Figure 13-15 It can be seen that the cycle performance of the regenerated electrode material after adding oxalic acid for surface modification during the mechanical activation process is effectively restored, which is significantly improved compared with Example 1, and is much higher than Example 2 without adding oxalic acid, and exceeds Comparative Example 2, confirming the effectiveness of the oxalic acid surface modification and repair technology.
[0082] The present invention further disassembles the batteries of Example 5 and Comparative Example 2 after cycling, and uses XPS detection technology to analyze the chemical composition of the CEI film on the electrode surface. The F 1s spectrum results are shown in FIG. Fig.16 The F 1s spectrum contains Li-F and Li x PO y F z , which is the main inorganic substance in the CEI film formed on the electrode surface during the cycle; in addition, the peak near 688eV is CF, which mainly comes from the polyvinylidene fluoride (PVDF) binder under the CEI film. By fitting the peak area, it is found that the Li x PO y F z It is in a dominant position, accounting for about 71.9%, while the LiF peak on the electrode surface of Comparative Example 2 is as high as 81.5%. Excessive LiF content indicates more serious electrolyte decomposition, forming a high impedance layer, hindering the migration of lithium ions in the CEI layer, and is not conducive to the cycle stability of the positive electrode. Therefore, the surge in LiF content on the electrode surface of Comparative Example 2 after cycling is also the key reason for restricting its cycle performance. This result also illustrates the importance of removing the LiF impurity phase during the repair process.
[0083] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for regenerating waste positive electrode materials by surface modification with oxalic acid, characterized in that: The following steps are involved: (1) separating and drying the waste positive electrode material and the oxalic acid solution after ball milling to obtain a modified material; (2) The modified material and a lithium source are mixed and calcined to obtain a regenerated positive electrode material.
2. The method for regenerating waste positive electrode materials by surface modification with oxalic acid according to claim 1, characterized in that: The ball milling speed is 450-500 rpm and the duration is 25-35 min; The ball-to-material ratio of the ball milling process is (18-28):
1.
3. The method for regenerating waste positive electrode materials by surface modification with oxalic acid according to claim 1, characterized in that: The oxalic acid solution is prepared by mixing oxalic acid and water in a ratio of (0.1-0.75) g: (30-70) ml.
4. The method for regenerating waste positive electrode materials by surface modification with oxalic acid according to claim 1, characterized in that: The molar ratio of the waste positive electrode material and oxalic acid is (1.4-2.8):
5.
5. The method for regenerating waste positive electrode materials by surface modification with oxalic acid according to claim 1, characterized in that: The surface of the modified material is formed with an oxalate coating layer with a thickness of 1.2-2.8 nm, and the morphology is single crystal particles. The particle size of the single crystal particles is 0.5-2 μm.
6. The method for regenerating waste positive electrode materials by surface modification with oxalic acid according to claim 1, characterized in that: The molar ratio of the lithium element in the lithium source to the transition metal element in the waste positive electrode material is (1-1.1):1; The lithium source includes one or more of lithium hydroxide, lithium carbonate and lithium nitrate.
7. The method for regenerating waste positive electrode materials by surface modification with oxalic acid according to claim 1, characterized in that: The calcination includes a first calcination and a second calcination performed sequentially; The temperature of the first calcination is 450-550° C., and the time is 1.5-2.5 hours; the temperature of the second calcination is 800-900° C., and the time is 13-17 hours.
8. The method for regenerating waste positive electrode materials by surface modification with oxalic acid according to claim 1, characterized in that: The waste positive electrode material comes from a nickel-cobalt-manganese ternary lithium battery.
9. The method for regenerating waste positive electrode materials by surface modification with oxalic acid according to any one of claims 1 to 8, characterized in that: The separation and drying also include washing and centrifugation steps.
10. A regenerated positive electrode material prepared by the method for regenerating waste positive electrode materials by surface modification with oxalic acid as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Recovery method for waste lithium cobalt oxide anode material
CN111455176A
Recycling method of nickel cobalt lithium manganate battery, regenerated nickel cobalt lithium manganate material and application
CN113113690A
Efficient leaching method of waste lithium iron phosphate positive electrode material
CN114196821A
Efficient recycling and reusing method of waste lithium ion battery positive electrode material
CN118137003A